Polycystic Ovary Syndrome and Infertility [Síndrome de Ovario Poliquístico E Infertilidad] - Vanhauwaert-Sudy, P (Ediciones Doyma, S.L., 2021)
Infertility is one of the main manifestations of the polycystic ovary syndrome (PCOS), and to day PCOS is the main cause of anovulatory infertility accounting for 80% of the cases. The majority of PCOS causes of infertility are treatable, and early diagnosis improves the patient s fertility outcome. In spite of its incidence and importance, the physiopathological mechanisms of PCOS are still relatively unknown. Recently an international evidence base recommendation for treatment have been published. © 2021
Keywords: Polycystic Ovary Syndrome; Infertility; Hyperandrogenism; Anovulation; Insulin Resistance